Longitudinal visceral muscles in Drosophila fully dedifferentiate and fragment prior to their reestablishment during metamorphosis - Schultheis, Dorothea; Frasch, Manfred (microPublication biology, 2023)
Although the Drosophila longitudinal visceral muscles have been shown to undergo major morphological changes during the transition from larval to adult gut musculature, there have been conflicting views as to whether these muscles persist as such during metamorphosis or whether they are built anew (Klapper 2000; Aghajanian et al. 2016). Here we present our independent analysis using HLH54Fb-eGFP as a cell type specific marker, which strengthens the proposition by Aghajanian et al. (2016) that the syncytial larval longitudinal gut muscles completely dedifferentiate and fragment into mononucleated myoblasts during pupariation before they fuse again and redifferentiate to form the adult longitudinal gut muscle